Short pulse fiber laser based on pure metal saturable absorber / Ahmad Razif Muhammad - Ahmad Razif , Muhammad (2019)
Pulsed fiber laser offers numerous applications in various fields such as high-precision material processing, bio-medicine, and range finder applications. This report focused on the development of pulse fiber laser that operates in three main different regions namely 1-, 1.55- and 2- micron region. The lasers utilized the all-fiber configuration in conjunction with Ytterbium doped fiber (YDF), Erbium doped fiber (EDF) and Thulium doped fiber (TDF) to produce an optimized laser at 1-,1.55- and 2 microns respectively. To realize the Q-switch pulse laser operation, metal based saturable absorber was fabricated and coated onto the surface of polyvinyl alcohol PVA thin film that act as the base material. These elements pick up a great interest amongst scientific researchers as they hold a unique optical property such as ultrafast response time, broad saturable absorption band and large third-order nonlinearity. Later, metal SA is sandwiched in between two fiber ferrule ends to form a device compatible saturable absorber for pulse generation. A Q-switched pulse was successfully demonstrated in all three regions with different output performance. These SAs were characterized in term of nonlinear absorption parameters. Together with field emission scanning electron microscopy (FESEM), energy dispersion X-ray (EDX), and linear absorption measurement. The output performance in terms of pulsed laser generation were analyzed and discussed. For instance, Q-switched fiber laser were successfully generated by all these materials namely, Ti-SA, Au-SA, and Cu-SA at all three regions. In addition, mode-locking behavior were realized in TDF (2-micron) region when Cu-SA applied in the cavity. These finding shows that metal material have a great potential for photonic applications.